Plastic pollution and environmental education through artwork - Helen Powers; Kofi Renner; Victoria Prowse (Cambridge Prisms: Plastics, 2024)
Plastics have benefited society, but their environmental impact has caused concerns since the 1970s. By the year 2050, plastic production is predicted to reach 26,000 million tonnes and generate 13,000 million tonnes of waste. Plastic in the environment impacts living organisms with short to long-term consequences. To address this, governmental policies, advocacy and recycling have been implemented with varying success. Environmental education plays an important role in mitigating some impacts of plastic pollution. Upcycling discarded plastics in artwork supports that endeavour. The art installation “Regulated Exhibition – The Plastic Human”, a collaboration between BACKLIT gallery, Joshua Sofaer and the Environment Agency, brought the artworld and environmental advocacy together, to inspire discussions on the narrative of plastic pollution. To bring the project to life BACKLIT gallery was turned into a factory where audience members could explore and interact with the installation. The exhibition was free, open to all and accessible to diverse demographics within Nottingham. The interactive exhibition provoked visitors’ senses and provided a feedback mechanism. The “Plastic Human” reflected the impacts of plastic pollution in our environment. Addressing plastic pollution is thought to cause a philosophical and/or ethical burden on humans. The measured and qualitative impact of this could impact our daily lives.